Uso de computadoras en problemas de circulación y dispersión en aguas costeras, lagos y ríos - Ayala Milian, Gustavo; Hiriart, Gerardo; Martínez Pereda, Pedro (My University, 1978)
The topic of computational fluid mechanics does not have a long history, by the 1930's there were only a limited number of papers on this topic, a condition that was due not only to the absence of high speed computational facilites but also to dificulties in dealing with the inherent nonlinearity of mos problems of interest. Thus, computational fluid mechanics has developed in tandem with the finite element method.
Keywords: equilibrium equation; kinematic; stress-strain; lake circulation analysis; finite element analog; simulation of water; method of weighted residuals